2015
DOI: 10.17302/tmg.1-1.10
|View full text |Cite
|
Sign up to set email alerts
|

The Black Death and the Future of the Plague

Abstract: This essay summarizes what we know about the spread of Yersinia pestis today, assesses the potential risks of tomorrow, and suggests avenues for future collaboration among scientists and humanists. Plague is both a re-emerging infectious disease and a developed biological weapon, and it can be found in enzootic foci on every inhabited continent except Australia. Studies of the Black Death and successive epidemics can help us to prepare for and mitigate future outbreaks (and other pandemics) because analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…2 Note that, to complicate matters, in the plague literature the term "pandemic" is also used to distinguish between a "First Pandemic", which would have started with Justinian's plague of 540-41 but would have included a series of outbreaks until around 750, when the infection disappeared from Europe and the broader Mediterranean area, and a "Second Pandemic" which started with the Black Death but also included a string of later outbreaks that ended only in the early nineteenth century (Kohn 2007;Little 2007;Alfani and Murphy 2017). Finally a "Third pandemic" originated in China, in the Yunnan area, towards the end of the nineteenth century and is still ongoing (Ziegler 2015;Alfani and Murphy 2017;Welford 2018). In this article, when referring to plagues the term "pandemic" will be used…”
Section: Epidemics Pandemics and The Black Death: Some Preliminary Cl...mentioning
confidence: 99%
“…2 Note that, to complicate matters, in the plague literature the term "pandemic" is also used to distinguish between a "First Pandemic", which would have started with Justinian's plague of 540-41 but would have included a series of outbreaks until around 750, when the infection disappeared from Europe and the broader Mediterranean area, and a "Second Pandemic" which started with the Black Death but also included a string of later outbreaks that ended only in the early nineteenth century (Kohn 2007;Little 2007;Alfani and Murphy 2017). Finally a "Third pandemic" originated in China, in the Yunnan area, towards the end of the nineteenth century and is still ongoing (Ziegler 2015;Alfani and Murphy 2017;Welford 2018). In this article, when referring to plagues the term "pandemic" will be used…”
Section: Epidemics Pandemics and The Black Death: Some Preliminary Cl...mentioning
confidence: 99%
“…Since ancient times, our planet has been suffering from the many pandemics and chronic diseases that afflict it, and which have claimed the lives of a large number of people and caused great crises that took a long time to overcome. When back to previous years, it is observed that the world witnessed a dangerous pandemic in the 14th century, which is the black plague (Black Death) that killed between 75 to 200 million people and is believed to have originated in or near China, then moved to Italy and then to the rest of Europe, and then to various nations [1] [2]. In 1521, smallpox appeared and killed more than 56 million people [3], while cholera killed more than a million people around the world between 1817 and 1923 [4] [5].…”
Section: Introductionmentioning
confidence: 99%